Optimization of logic threshold control strategy for electric vehicles with hybrid energy storage system by pseudo-spectral method. (October 2018) - Yang, Guodong; Li, Junqiu; Fu, Zijian; Fang, Linlin
Abstract: A traditional logic threshold control strategy (LTCS) is proposed but simulation results show control effects have a large gap with pseudo-spectral optimal results. To narrow this gap, the optimization is analyzed, the power relationship between the hybrid energy storage system (HESS) and the vehicle load is determined and the optimal power distribution between the battery and the ultra-capacitor is obtained. A near-optimal LTCS is presented using valuable control rules extracted by analyzing optimal control actions. The near-optimal LTCS can fully use high power characteristics of ultra-capacitor, avoid battery being damaged by high charge and discharge current, and make battery SOC consumption decreased by 2.0%. The hardware-in-the-loop (HIL) experiment is carried out and further validates that the near-optimal LTCS is real-time and reliable.